Kajian Terhadap Risiko Pada Jual Beli Benda Bergerak - Bing Waluyo (Wijayakusuma Law Review, 2022)
Risk is the obligation to bear losses as a result of an event (event) that befalls the object of the agreement beyondthe fault of one of the parties. Based on this understanding, it can be seen that the issue of risk stems from theoccurrence of events beyond the fault of one of the parties to the agreement. This event in contract law is called astate of coercion (overmacht; force majeure). Thus, the issue of risk is the aftermath of the problem of coercivecircumstances (overmacht; force majeure), which is an event that is unintentional, cannot be predicted orknown, and is beyond the power of the compelling debtor. When viewed from the type, the state of coercion canbe divided into two, namel An absolute/absolute force majeure situation, and A situation of compulsion(overmacht; force majeure) that is relative, Regarding the risks in buying and selling movable objects, in the CivilCode there are three regulations, namely Regarding certain objects (Article 1460 of the Civil Code), Regardingobjects sold according to weight, quantity or size (Article 1461), and Regarding the objects for sale which aresold according to piles (Article 1462). Based on Article 1462 of the Civil Code, the risk of the object lies with thebuyer.